2010
DOI: 10.2174/187152610793180902
|View full text |Cite
|
Sign up to set email alerts
|

Opisthorchiidosis-A Review

Abstract: The discovery history of opisthorchiid flukes dates back more than 200 years. The life cycle of these liver flukes includes prosobranch snails as the first and a big variety of freshwater fish as the second intermediate hosts. Opisthorchis felineus, O. viverrini and Clonorchis sinensis are species of major medical importance, while sporadic cases of human infection with other representatives of this family are also documented in the literature. There are estimations that 17 million people are infected and more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 85 publications
0
12
0
1
Order By: Relevance
“…For example, microscopic examination is cumbersome and time consuming, requiring experienced laboratory technicians, and often it is difficult to distinguish eggs from those of closely related heterophyids, which have similar egg morphologies. Eggs can therefore only be characterised as “ Opisthorchis/Clonorchis -like” eggs [10]. Crude or recombinant antigens have been evaluated for immunodiagnosis; however, the specificity and sensitivity of these methods are still in great need of improvement [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, microscopic examination is cumbersome and time consuming, requiring experienced laboratory technicians, and often it is difficult to distinguish eggs from those of closely related heterophyids, which have similar egg morphologies. Eggs can therefore only be characterised as “ Opisthorchis/Clonorchis -like” eggs [10]. Crude or recombinant antigens have been evaluated for immunodiagnosis; however, the specificity and sensitivity of these methods are still in great need of improvement [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…In the European Union, sporadic infections have been reported in Greece and in Germany [4,5]. The acute infection is described as an association of fever, cutaneous rash, abdominal pain, diarrhoea, nausea and vomiting, with or without jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the natural definitive hosts of O. viverrini include human, dogs, and cats (Schuster 2010). For animal model, Syrian hamster have been used (Hutradilok et al 1983;Boonjaraspinyo et al 2011), and recently, gerbils have also been recognized (Boonmars et al 2009a, b;Wonkchalee et al 2011).…”
Section: Discussionmentioning
confidence: 99%